2008
DOI: 10.1007/s10560-008-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Romanian Adoptees and Pre-adoptive Care: A Strengths Perspective

Abstract: Ninety-one parents of 120 adopted Romanian children who were part of a longitudinal study were surveyed to determine perceptions of their relationships with their children, their adoption experiences, and the children's strengths. The Behavioral and Emotional Rating Scale (BERS) was used and parents were easily able to rate their children's emotional and behavioral strengths. Levels of parentchild relationship satisfaction were the most consistent predictors of child emotional and behavioral strength. The chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Another key variable to consider in adoption research is the age at which the child is adopted. Among Romanian adoptees, children adopted after 24 months were at greater risk for higher levels of problem behaviors (Meese, 2005) and lower levels of behavioral and emotional strengths (Pearlmutter et al, 2008). Nevertheless, age at adoption in this sample was only predictive for Courage, with only a relatively trivial increase in likelihood of occurrence.…”
Section: Change and Continuity In Character Strengthsmentioning
confidence: 80%
See 1 more Smart Citation
“…Another key variable to consider in adoption research is the age at which the child is adopted. Among Romanian adoptees, children adopted after 24 months were at greater risk for higher levels of problem behaviors (Meese, 2005) and lower levels of behavioral and emotional strengths (Pearlmutter et al, 2008). Nevertheless, age at adoption in this sample was only predictive for Courage, with only a relatively trivial increase in likelihood of occurrence.…”
Section: Change and Continuity In Character Strengthsmentioning
confidence: 80%
“…Instead, existing studies mostly used a deficit-based approach to examining the problematic development of IA children with early orphanage rearing (see meta-analysis by . One exception was a strength-based study by Pearlmutter, Ryan, Johnson, and Groza (2008) who found children (with a mean age of 10 years old) adopted from Romania to have above average intrapersonal and affective strength. In view of the limited number of studies that have explored the character strengths of the adopted children, there is a need for a strength-based approach in studying post-adoption development.…”
Section: Adjustment Of Internationally Adopted Childrenmentioning
confidence: 99%
“…This is not particularly surprising given research ethics and the need for deep exploration of meaning with vulnerable populations, especially with international contexts and cross-cultural research. The exception to this was research in child development and institutionalization, identity formation and adjustment of adoptees, and adoptive parenting (e.g., Groza, 1999; Pearlmutter et al, 2008; S. D. Ryan & Groza, 2004) in which quantitative research incorporated larger data sets and standardized measures in addition to development of scales for measurement (Massatti et al, 2004; Mohanty, 2010).…”
Section: Methodological Approaches Employed By Social Workmentioning
confidence: 99%
“…Important investigations include identity development of Korean adoptees and family life (e.g., Bergquist, 2004;Bergquist, Campbell, & Unrau, 2003;Bergquist, Vonk, Kim, & Feit, 2007;Kim, 1977;McGinnis, in press;Yoon, 2004), including the rarely researched topic of openness in ICA (Hayes & Kim, 2007). Also, there are important research results in the literature related to child transition from country of origin to the new adopted home and child development, including the institutional experience, especially in Romania (e.g., Gavrilovici & Groza, 2007;Groza, 1999;Pearlmutter, Ryan, Johnson, & Groza, 2008;S. D. Ryan & Groza, 2004).…”
Section: Perspectives On Identity Formation Family Transition and Child Developmentmentioning
confidence: 99%
See 1 more Smart Citation